2023
DOI: 10.1093/biosci/biad009
|View full text |Cite
|
Sign up to set email alerts
|

A Transdisciplinary Framework to Unlock the Potential Benefits of Green Spaces for Urban Communities Under Changing Contexts

Abstract: New urban models increasingly seek to create more sustainable, livable, and healthier cities by reinvigorating green space. In this article, we highlight and briefly review several main but disconnected areas of study in which the factors that frame human–environment interactions and therefore also influence the potential well-being outcomes of those interactions are studied. We then use the intersection of affordance theory and socio-institutional programming to provide a conceptual framework that ties togeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 112 publications
0
1
0
Order By: Relevance
“…It has also been shown that individuals who live near to greenspace tend to be more connectedness to nature 31 . The urban development sector could increase high-quality coverage of greenspaces in residential areas with social programs that help teach people how to engage with nature when in public greenspaces 32 34 . These investments may provide the supports to individuals to learn new ways to interact with nature or be mindful of natural elements in public green spaces even when the initial main goal of going to a public greenspace is a non-nature based activity 35 .…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that individuals who live near to greenspace tend to be more connectedness to nature 31 . The urban development sector could increase high-quality coverage of greenspaces in residential areas with social programs that help teach people how to engage with nature when in public greenspaces 32 34 . These investments may provide the supports to individuals to learn new ways to interact with nature or be mindful of natural elements in public green spaces even when the initial main goal of going to a public greenspace is a non-nature based activity 35 .…”
Section: Discussionmentioning
confidence: 99%